Platynota stultana Walsingham, 1884 a new record for Malta (Tortricidae: Tortricinae, Sparganothini) - Aldo Catania; Anthony Seguna; John J. Borg; Paul Sammut (SHILAP)
Platynota stultana Walsingham, 1884 is reported for the first time from the Maltese Islands. A Maltese name is proposed for this new record.